Specificity of Episodic Future Thinking in Adolescents: Comparing Childhood Maltreatment, Autism Spectrum, and Typical Development - Lau-Zhu, A; Chan, C; Gibson, D; Stark, E; Wang, J; Happé, F; Stacey, J; Cooper, M (Springer, 2024)
Maltreatment and autism can be associated with overlapping difficulties across functional domains (e.g., social, emotional, and sensory) and high rates of mental health problems. A cognitive approach focussing on affect-laden cognition, here on episodic future thinking (FT), could help inform cognitive assessments and adapt psychological interventions. Three groups of adolescents (N = 85), (i) maltreatment (n = 28), (ii) autism (n = 29), and (iii) typical development without maltreatment/autism (TD; n = 28), matched in age (10–16 years old), sex (assigned at birth), and socioeconomic status, completed a newly adapted online Autobiographical Future Thinking Test. As predicted, the maltreatment group generated significantly fewer specific future events relative to the TD group, however, the number of specific future events did not significantly differ between the autism and the other groups. Exploratory analyses showed that lower FT specificity was significantly associated with more depressive (but not anxiety) symptoms across the three groups. These findings shed light on the cognitive profiles of both maltreatment and autism during adolescence and signal FT as a potential therapeutic target for adolescents with these developmental differences. Our study lays the foundation for additional comparisons of maltreatment-related presentations versus autism with improved designs and a broader set of cognitive and clinical domains.